Mycotoxins in grains and feed: Contamination and toxic effect in animals - Pleadin J. (Biotechnology in Animal Husbandry, 2015)
Mycotoxins are secondary metabolites of moulds that represent a significant food safety issue and pose a risk to health and wellbeing of humans and animals, having a negative impact on economies all over the world. They can cause intoxication in animals and affect the less productive performance and nutritional value of animal feed. Also, mycotoxins may contaminate different types of food through directly and indirectly way and cause negative health effects in humans. To estimate the potential of their harmful effect it is necessary to know the terms of mycotoxins occurrence and frequency, toxicity and biotransformation in different animal species and humans, possibility of contamination prevention, and their inactivation or reduction in the case when the incidence is inevitable. The relatively small number of comparable data on the incidence of mycotoxins in feed from European countries show the necessity of systematic control and the application of validated analytical methods in their determination. This paper gives the overview of incidence of grains and feed contamination with most important and common mycotoxins and the evidenced toxic effects in animals.